Réponses

  • x22
  • Modérateur Junior
2014-09-26T19:18:32+02:00
Bonsoir,

A=12,5-4x(5,5-1,5)+0,5
=12,5-4x(4)+0,5
=12,5-4x4+0,5
=12,5-16+0,5
=-3,5+0,5
=-3

B=175-(8-14)+(2,39)
=175-(-6)+2,39
=175+6+2,39
=181+2,39
=183,39

C=((-3)x12):((-6)x2)
=(-36):(-6x2)
=(-36):(-12)
=3

Voilà
2014-09-26T19:30:39+02:00
A = 12,5 - 4 x ( 5,5 - 1,5 ) + 0,5
= 12,5 - 4 x 4 + 0,5
= 12,5 - 16 + 0,5
= - 3,5 + 0,5
= - 3

B = 175 - ( 8 - 14 ) + (2,39)
= 175 + 6 + 2,39
= 181 + 2,39
= 183,39

C = [ ( - 3 ) x 12 ] : [ ( - 6 ) x 2 ]
= - 36 : ( - 12 )
= 3